Effects and mechanisms of polysaccharides from natural medicinal plants on improving aerobic exercise capacity - Xu, Mingxin; Chen, Weiyu; Liang, Wenjian (Frontiers in Nutrition, 2025)
Aerobic exercise capacity is a critical determinant of endurance performance and overall health. Natural medicinal plant polysaccharides (NMPPs) have emerged as promising bioagents to enhance aerobic capacity through multi-target mechanisms. This review summarizes the effects of NMPPs on improving aerobic capacity, including oxygen supply and utilization in skeletal muscle, as well as the storage and metabolism of energy substrates. Additionally, we discuss the structural specificity related to their bioactivities. Furthermore, the mechanisms by which NMPPs enhance aerobic capacity encompass anti-fatigue properties, antioxidative effects, anti-inflammatory actions, immunomodulation, and modulation of gut microbiota. However, although there are many in vitro evidences, clinical translation requires standardized human trials and deeper exploration of structure-activity relationships. NMPPs represent a safe, multi-mechanistic alternative to conventional strategies, offering novel solutions for improving athletic performance and health resilience.